(untitled) (International Journal of Technology and Management Research, 2020)
Improved environmental management facilities provide social benefits to economic agents in Ghana. Biogas technology facility is one solution that offers societal gains. However, the maximization of social benefit in some cases depends on the structure of the market. The objective of this study was to examine loss in consumer surplus and gain in producer surplus, and if there was, deadweight loss relating to regulated biogas market structure in Ghana. The simple market models were fundamental tools in the economic surplus method used for the study. The results of the study showed that regulated monopoly although productive reduces societal gains and so inefficient compared with the free market. The regulated monopolist‖ producer gain was 13%, but there was 37% and 41% loss to consumers and investors‖ NPV respectively. There was also a deadweight loss of US18,140.00. Market forces allow consumers to be future regulators of previously government regulated 2nd and 3rd degree discriminating monopoly. It is possible to avoid Market forces regulation in biogas diffusion when participants are reluctant to hike price.